Impact of corruption on the effectiveness of official development assistance in CEMAC Zone - DSANGUE TCHANA Christianne Laure; Nembot NDEFFO Luc; DAZOUE DONGUE Guy Paulin (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The purpose of this paper is to check the impact of corruption on the link between development assistance and economic growth in the countries of the CEMAC Zone. Thus, from our dynamic panel data model relating economic growth and the explanatory variables including official development assistance and the index of corruption, we use the Generalized Moments Method (GMM) to estimate our model; our sample consisting of the six countries of the CEMAC Zone (Cameroon, Congo, Gabon, Equatorial Guinea, Central African Republic and Chad) and our study period extends from 1996 to 2013. The results indicate that public support for short-term development has no significant effect on growth in the CEMAC Zone; on the contrary, public aid to long-term development has a positive and significant effect on economic growth. Moreover, the variable of interaction between public aid for short-term development and corruption has a negative and significant effect on growth while the long term, has a positive and significant effect on growth. This implies that long-term control strategies against corruption have achieved results such as flows of official development assistance have a positive impact on growth. It therefore appears urgent for the leaders of recipient countries to strengthen the fight against corruption to improve the impact of aid on growth in the CEMAC Zone